2021
DOI: 10.3390/medicina57060621
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β Physiology as a Novel Therapeutic Target Regarding Autoimmune Thyroid Diseases: Where Do We Stand and What to Expect

Abstract: Transforming growth factor beta (TGF-β), as a master regulator of immune response, is deeply implicated in the complex pathophysiology and development of autoimmune thyroid diseases. Based on the close interplay between thyroid autoimmunity and TGF-β, scientific interest was shifted to the understanding of the possible role of this molecule regarding the diagnosis, prognosis, and therapy of these diseases. The main aim of this review is to present research data about possible treatment options based on the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 69 publications
0
7
0
3
Order By: Relevance
“…TGF-β plays a pivotal role in normal human immune response and is involved in the pathophysiological spectrum of thyroid autoimmunity [ 5 , 13 , 17 , 43 ]. Based on the clear interplay between TGF-β, EMT, and primary ciliogenesis [ 30 , 31 , 33 , 40 , 41 ], we studied EMT markers in AITD and found that thyroid follicular cells can acquire mesenchymal markers and still preserve their epithelial phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β plays a pivotal role in normal human immune response and is involved in the pathophysiological spectrum of thyroid autoimmunity [ 5 , 13 , 17 , 43 ]. Based on the clear interplay between TGF-β, EMT, and primary ciliogenesis [ 30 , 31 , 33 , 40 , 41 ], we studied EMT markers in AITD and found that thyroid follicular cells can acquire mesenchymal markers and still preserve their epithelial phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblast between the second and fifth passages were used for analysis. [20][21][22][23] For adipogenesis, cells were cultured in serum-free DMEM supplemented with T3, insulin (Boehringer-Mannheim, Mannheim, Germany), carbaprostaglandin (cPGI2; Calbiochem, La Jolla, CA, U.S.A.), and dexamethasone. A peroxisome proliferator-activated receptor gamma agonist, rosiglitazone (10 μM; Cayman, Ann Arbor, MI, U.S.A.), was also added from day 1 of differentiation for heightened stimulation of adipogenesis.…”
Section: Methodsmentioning
confidence: 99%
“…ЭОП -аутоиммунное заболевание, осложняющее течение БГ. Глюкокортикоидная терапия является методом выбора лечения ЭОП, благода-ря ее противовоспалительному и иммуносупрессивному действию [10,18,22,24]. Частота положительного ответа на лечение наблюдается не у всех пациентов.…”
Section: заключениеunclassified